Glutaryl kappa-carrageenan: synthesis, characterization and investigation of potential as gel-based biopolymer electrolyte - Pongali, Priyatharshiny; Kasim, Norherdawati; Hanibah, Hussein; Aminuddin Rosli, Nurul Hazwani; Rani, Mohd Saiful Asmal; Mohd Noor, Siti Aminah; Abdullah, Norli; Shamsudin, Intan Juliana (Springer Science and Business Media Deutschland GmbH, 2025)
A novel kappa-carrageenan derivative, glutaryl kappa-carrageenan (G-κCar) was successfully produced via nucleophilic substitution reaction. The introduction of glutaric anhydride (GA) into the kappa-carrageenan (κCar) matrix had markedly altered its chemical and electrochemical properties. Elemental analysis showed that the GA substitution led to an increased oxygen percentage in G-κCar as compared to pure κCar. The highest degree of substitution obtained was 4.14 in 3 gGA-κCar/48 h synthesized sample. The successful substitution of GA molecule into κCar polymeric chain was confirmed by the FTIR analysis based on the formation of a new carbonyl (C=O) bond in the G-κCar spectra. The 1H-NMR analysis further proved the GA substitution by the appearance of new multiple resonance peaks at δ = 1.70–2.75 ppm, which belonged to the characteristic signals of protons in the anhydride group. TGA thermograms showed lower degradation temperature in the synthesized G-κCar due to disruption of both intermolecular and intramolecular hydrogen bonds in the G-κCar polymeric chains. The substitution of GA also improved the ionic conductivity of G-κCar up to 4.63 × 10−3 S cm−1 at ambient temperature. Cyclic voltammetry plots demonstrated that the 3 gGA-κCar/48 h sample had a larger background current than κCar which indicated that the synthesized 3 gGA-κCar/48 h biopolymer had an improved effective surface area. Linear sweep voltammetry (LSV) analysis revealed the increased electrochemical potential in G-κCar as compared to the pristine κCar. The highest potential obtained was 1.95 V for 3 gGA-κCar/48 h sample. The transference number for 3 gGA-κCar/48 h was calculated to be 0.98 over five continuous hours. This implied that ionic conduction in the gel was predominantly driven by ions, with the contribution of electrons being minimal and therefore negligible. This study highlighted how this functionalization enhanced the characteristics of κCar, potentially expanding G-κCar applications as a gel biopolymer electrolyte in electrochemical systems.